Budowanie właściwych wzorców żywieniowych u otyłego dziecka. Studium przypadku - Słoma, Małgorzata; Szeja, Nicola; Adamek, Brygida; Krenzel, Izabella (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
One of the most common health and economic problems in developed countries is the issue of overweight. The aim of the study was to evaluate the effect of individual dietary intervention on weight reduction and build proper nutritional patterns in obese children. A boy at age 11 was referred by a pediatrician to a Metabolic Disorders and Obesity Disorders Clinic. At the time of the first visit, the body weight of the patient was 68.7 kg with a height of 1.54 m (value above 97 centile of the OLAF program, obesity). Analysis of the food diary from the seven days before the visit, developed jointly by the patient and his mother, revealed excessive energy supply relative to daily requirements and an incorrect composition of the daily ration. For a half-year period, a balanced diet with a daily caloric deficit of 300 kcal was introduced. During regular follow-up visits, the nutritional education of the child and parents was further enhanced, and the importance of daily physical activity in the treatment and prevention of obesity. After six months of dieting, weight reduction was achieved. Proper dietary patterns have been implemented to the patient and his immediate family. Comprehensive education has resulted in the implementation of daily physical activity. This cannot only be an emergency intervention but also a basis for the prevention of obesity and its complications
Keywords: otyłość; dziecko; wzorce żywieniowe; dieta ubogoenergetyczna